Students’ knowledge and attitude on preventive behaviour of Zika disease - Abdul Rahman, Mahirah; Mohd Jais, Norhani; Wok, Saodah (Global Academy of Training & Research (GATR) Enterprise, 2017)
Warm and humid Malaysia has always been vulnerable to mosquito-borne diseases like Zika. So, practicing preventive behaviour is the defence against the disease. The purpose of this paper is to identify knowledge and attitude on preventive behaviour of the Zika disease. Using the Social Learning Theory, the present study aims: (1) to evaluate levels of knowledge, attitude and preventive behaviour on Zika disease; (2) to examine the relationships between knowledge and attitude with preventive behaviour; and (3) to determine the best predictor for Zika preventive behaviour. This study employs the quantitative research design using the survey method. Data were collected using the self-administered questionnaire. A total of 207 students from a public university participated in the study. The levels of knowledge, attitude and preventive behaviour are high. There are positive correlations among knowledge, attitude and preventive behaviour. Attitude is the best predictor for preventive behaviour. With knowledge and positive attitude towards the disease, the preventive behaviours are practiced. This suggests that future health campaigns on Zika disease prevention should focus on enhancing knowledge and cultivating positive attitude to encourage preventive behaviour among students.